STRUCTURE OF ROLLING FORECAST BUDGETING IN MODERN BUDGETING AND ITS IMPORTANCE FOR BUSINESSES IN CHANGING ECONOMIC CONDITIONS: A SAMPLE APPLICATION - Özdemir, Serkan (My University, 2021)
Budgets are a financial design activity related to what needs to be done to carry out the planned activities. The concept of rolling budget, which appears as an alternative to traditional budgeting, does not depend on a certain period and end date, unlike the static structure of traditional budgets. In the rolling budget approach, budgets can be revised weekly, monthly or quarterly depending on the needs of the businesses, regardless of the accounting period. In the method, a new budget period is added to the ending week, month or quarterly period until the end of the next year. Thus, the operating budget is updated and adapted to changing economic conditions. Businesses may encounter many unexpected threats or opportunities in today's world conjuncture. The rolling budget approach allows businesses to adapt to changing conditions in the shortest time in terms of budget. With this study, the functioning structure of the rolling budgeting technic is tried to be explained through a sample application. In this way, it is aimed to raise awareness about the applicability of the budgeting method rolling in the enterprises.
Keywords: Budgeting; Modern Budgeting; Rolling Forecast Budgeting; Dynamic Budgeting; Continuous Budgeting